LEGITIMATE POWER AS A MEDIATOR OF THE INFLUENCE OFKNOWLEDGE AND PROCEDURAL JUSTICE ON TAX COMPLIANCE - Mulyani, Susi Dwi; Levana Dhia Prawati; Amalia Puspita Wardhani; Hamzah, Noradiva (Media Riset Akuntansi, Auditing & Informasi, 2024)
This study analyzes the influence of taxpayer knowledge and procedural justice on tax compliance. This study also analyzes the role of power legitimacy as a mediating variable. Legitimacy of power is expected to mediate the influence of taxpayer knowledge and procedural justice in increasing taxpayer compliance. This research is quantitative research that tests hypotheses using primary data through distributing questionnaires. The population in this research is individual taxpayers who carry out business activities and tax consultants who are members of the Indonesian Tax Consultants Association (IKPI). The sampling technique uses convenience sampling. Hypothesis testing uses SEM PLS statistical tools by conducting path analysis tests to obtain results of the direct influence of taxpayer knowledge and procedural justice on tax compliance and the indirect influence, namely taxpayer knowledge and procedural justice on tax compliance through the mediating variable power legitimacy. These results of hypothesis testing prove that taxpayer knowledge and procedural justice each have a positive effect on power legitimacy and tax compliance. Besides that, power legitimacy also plays a role in mediating the influence of knowledge and procedural justice on tax compliance. This research can prove the theory of planned behavior that the behavior shown by a person arises because of the individual's inner intention to behave. The research implication from the theoretical aspect is that it can prove the role of power legitimacy as a mediating variable that links the influence of knowledge and procedural justice on tax compliance.